Airway Compromise due to Retropharyngeal Emphysema–A Rare Complication of an Extravasated Peripherally Inserted Central Venous Catheter. (16th October 2019) - Licina, Ana
Abstract : A 48-year-old woman was scheduled for flexible bronchoscopy, video-assisted thoracoscopic surgery and mediastinal washout. She had developed voice changes, difficulty swallowing, shortness of breath with a fever and increased respiratory rate in intensive care unit 12 days after a double liver and kidney transplantation. Computerised tomography of neck and chest demonstrated extensive retropharyngeal and subcutaneous emphysema, laryngeal distortion and pneumo-mediastinum; however, the causative factors were not immediately obvious. Intraoperatively, an un-anticipated diagnosis of extravasated peripherally inserted central venous cannula (PICC) was made. Total parenteral nutrition had extravasated into the mediastinum and thorax. Subsequent inflammation and infection resulted in air pocket formation. The retropharyngeal air pockets were caused by mediastinal emphysema tracking through the tissue planes to the anterior and posterior larynx. Awareness of the tip position and accompanying clinical and radiological enquiry, must be performed prior to use of PICC lines in critically ill patients.